The Clinical Approach on Receipt of an Unexpected Laboratory Test Result - Masood A; Karim MY (International Journal of General Medicine, 2020)
Amina Masood,1 Mohammed Yousuf Karim2 1Locum General Practitioner, The Cambridge Practice, Aldershot, UK; 2Immunology Laboratory, Department of Pathology, Sidra Medicine, Doha, QatarCorrespondence: Mohammed Yousuf Karim Department of Pathology, Sidra Medicine, Al Luqta St, Doha 26999, QatarTel +974 4003 2968Email mkarim@sidra.orgAbstract: Approximately 70% of all healthcare decisions affecting diagnosis and treatment involve the use of tests performed within pathology laboratories. The utilisation of diagnostic laboratory services continues to increase, with growth both in volume of tests requested, as well as in the breadth of test repertoire. Every year in the United Kingdom, approximately 1 billion tests are run in hospital laboratories, equivalent to 14 tests per person. Fifty million tests are requested in primary care. Accordingly, there is an inevitable increase in the number of unexpected laboratory results which clinicians review. This is an important, and potentially time-consuming, issue, which we considered to merit a more detailed discussion. Unexpected laboratory results may be critical or non-critical in nature. They may be absolutely genuine, reflecting a clinical change in the patient’s condition, a differential diagnosis not previously considered, or an additional test specifically added by the laboratory. However, such results may also occur due to a variety of different circumstances, including much more rarely laboratory error. As there is little published evidence or guidance available, herein we discuss aspects of the clinical approach for physicians after receiving an unexpected laboratory test result.Keywords: pathology, critical, non-critical, error, communication, diagnosis, assay